(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Nowadays the materials made by methods of powder metallurgy are widely used for producing details of the heavy-duty friction pair. Due to high reliability and effective combination of mechanical and tribological properties such materials are usually used in transport industry, for example for gear assemblies of different kinds of automobiles, brake system of high speed trains, aircrafts etc. There are many variations of powder materials, but for friction pairs the iron based antifriction materials, for example Fe-C-Cu, Fe-P, Fe-Cu-Sn, Fe-Cu-Sn-Pb-MoS2, Fe-C-Cu-Ni-Mo and others are successfully used. In recent years, the requirements for antifriction materials are raised highly because of more intensive freight traffic and speed of vehicles. On the other hand, the demand of more inexpensive materials and effective using of natural resources is the issue of the day.The aim of this paper is to offer the new low-cost metal powder material based on Fe-C compound with content of Ni and Mo up to 0.3%. The influence of the parameters of technological process (pressing and sintering) on physical properties (porosity, density), mechanical properties (hardness) as well as on 2D roughness and 3D texture parameters was studied and is presented in this paper as well. The “Taylor Hobson Ltd” 3D measurement system has been used in metrological study. The analysis of the influence of the technological process on the surface roughness parameters is given. The tribological properties (friction coefficient) were evaluated using “ball-on-disk” testing without lubrication. The analysis of achieved results is prove the appropriateness of using of new low-alloy metal powder material on the iron base for producing details of friction pair. One of the possible applications - bushes for braking systems of railway rolling stock. Using offered material allows reducing the product cost in complex with acceptable wear resistance and durability.